2020
DOI: 10.3390/molecules25184064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Silico and In Vitro Evaluation of Some Flavone Derivatives for Acetylcholinesterase and BACE-1 Inhibitory Activity

Abstract: Acetylcholinesterase (AChE) and β-secretase (BACE-1) have become attractive therapeutic targets for Alzheimer’s disease (AD). Flavones are flavonoid derivatives with various bioactive effects, including AChE and BACE-1 inhibition. In the present work, a series of 14 flavone derivatives was synthesized in relatively high yields (35–85%). Six of the synthetic flavones (B4, B5, B6, B8, D6 and D7) had completely new structures. The AChE and BACE-1 inhibitory activities were tested, giving pIC50 3.47–4.59 (AChE) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…For instance, Lee et al analyzed several phlorotannins that interacted also with some of the residues above referred, especially eckol (Figure 7) [53]. Kashyap et al observed that two plant natural compounds, reserpine and ajmalicine (Figure 7), also interacted with some of the most rele- Similar to what occurs for synthetic compounds, flavone derivatives (PDB#6EQM), specifically baicalein and diosmetin derivatives [57], 2-phenylbenzimidazoles (PDB#1FKN) [58], 7,8-dihydroxyflavone derivatives (PDB#2ZHS) [59], molecular hybrids of 2-pyridylpiperazine and 5-phenyl-1,3,4-oxadiazoles (PDB#2ZJM), especially compound 4 [60], and quinazolinonebased hydrazones (PDB#4B70) [61], also have demonstrated very promising in silico results that can result in novel drug candidates for BACE-1 inhibition, as shown in (Figure 8). Tran et al [62] built a 2D-QSAR model (R 2 of 0.83) based on the structure of BACE-1 inhibitors found in the literature to identify novel potential inhibitors in a library of chalcone derivatives.…”
Section: β-Secretasementioning
confidence: 80%
“…For instance, Lee et al analyzed several phlorotannins that interacted also with some of the residues above referred, especially eckol (Figure 7) [53]. Kashyap et al observed that two plant natural compounds, reserpine and ajmalicine (Figure 7), also interacted with some of the most rele- Similar to what occurs for synthetic compounds, flavone derivatives (PDB#6EQM), specifically baicalein and diosmetin derivatives [57], 2-phenylbenzimidazoles (PDB#1FKN) [58], 7,8-dihydroxyflavone derivatives (PDB#2ZHS) [59], molecular hybrids of 2-pyridylpiperazine and 5-phenyl-1,3,4-oxadiazoles (PDB#2ZJM), especially compound 4 [60], and quinazolinonebased hydrazones (PDB#4B70) [61], also have demonstrated very promising in silico results that can result in novel drug candidates for BACE-1 inhibition, as shown in (Figure 8). Tran et al [62] built a 2D-QSAR model (R 2 of 0.83) based on the structure of BACE-1 inhibitors found in the literature to identify novel potential inhibitors in a library of chalcone derivatives.…”
Section: β-Secretasementioning
confidence: 80%
“…All chemicals were obtained from commercial suppliers and used without further purification. Melting points determination, UV (ultraviolet), IR (infrared), HR-MS (high-resolution mass spectrometry), 1 H-NMR (proton nuclear magnetic resonance), and 13 C-NMR (carbon-13 nuclear magnetic resonance) spectra elucidation and all computation processes were performed on the systems as described earlier [16].…”
Section: Methodsmentioning
confidence: 99%
“…Assay. AChE inhibitory activity was determined using the materials and methods as described earlier [16]. e initial mixture in each well consisted of phosphate buffer pH 8, sample (studied compounds or reference) prepared at different concentrations in dimethyl sulfoxide, and AChE enzyme solution 0.25 UI/mL (in phosphate buffer).…”
Section: Acetylcholinesterase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences from available literatures confirmed existing drugs against the receptors identified. Pepstatin inhibits Cathepsin-D (Knight and Barrett 1976;Fox et al 2016), belnacasan and z-yad-fmk are inhibitors of Caspase-1 (MacKenzie et al 2010;Chopra et al 2009), crytotanshinone, niclosamide and napabucasin inhibit STAT3 (Li et al , 2013(Li et al , 2020, Phenserine inhibits BACE2 (Chang et al 2017), BACE1 inhibited by elenbecestat and umibecestat (Adewole and Ishola 2021;Tran et al 2020), aliskiren strongly binds and inhibits Renin (Wal et al 2011), SRC inhibited by kx-2391, bosutinib and saracatinib (Naing et al 2013, Vultur et al 2008Gucalp et al 2011), ulixertinib and ravoxertinib inhibit MAPK1 (Braicu et al 2019), enalapril, benazepril inhibit ACE (Jackson et al 1984;Yu et al 2006), hydroxychloroquine inhibits ACE2 (Fu et al 2021), HMG-CoA, rosuvastatin and simavastatin targeted against HMG-CoA (Abletshauser et al 2002;Slater and MacDonald 1988) and hydroxyurea inhibits RDR (Keikhaei et al 2016;Singh and Xu 2016).…”
Section: Existing Drug Candidates Against the Human Receptorsmentioning
confidence: 99%